2007
DOI: 10.3844/ajassp.2007.390.396
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Polyethylene in Hot Asphalt Mixtures

Abstract: The increase in road traffic during the last two decades in combination with an insufficient degree of maintenance due to shortage in funds has caused an accelerated and continuous deterioration of the road network in Jordan. To alleviate this process, several types of measures may be effective, e.g., securing funds for maintenance, improved roadway design, use of better quality of materials and the use of more effective construction methods. The use of polymer in asphalt mixture as a modifier started in the 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(69 citation statements)
references
References 0 publications
4
63
0
2
Order By: Relevance
“…(5-d) shows a decrease of flow for all percents of HDPE except the percents of (3% HDPE and 6% HDPE) show an increase of flow results.This agrees well with the results of the penetration and kinematic viscosity for the HDPE modified binder presented in earlier sections. These results agrees with previous research that HDPE can improve the stability and flow of the HMA up to certain percentages then, negative impact starts to appear [3,5,12].…”
Section: 23effect Of Hdpe On Hma Marshall Test Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…(5-d) shows a decrease of flow for all percents of HDPE except the percents of (3% HDPE and 6% HDPE) show an increase of flow results.This agrees well with the results of the penetration and kinematic viscosity for the HDPE modified binder presented in earlier sections. These results agrees with previous research that HDPE can improve the stability and flow of the HMA up to certain percentages then, negative impact starts to appear [3,5,12].…”
Section: 23effect Of Hdpe On Hma Marshall Test Resultssupporting
confidence: 82%
“…Another research reported that the best results were obtained when polymer concentration was kept below 3% for HDPE and above this percent stability decreased [11].Another research used HDPE to coat the aggregate by using dry process. The recommended proportion of the modifier was 12% by the weight of bitumen content [5].Hinislioglu et al reported that HDPE modified asphaltic binders provide better resistance against permanent deformation, because of their higher stability and relatively lower flow. As a result, HDPE modified asphaltic binders were considered to be useful in mitigating permanent deformation in hot climate regions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Uses of recycled plastic in the construction industry include plastic strips to add to soil embankments, which has positive results of increasing the measured strength in reinforcement of soils. HMA mixture has a higher stability, reduced pavement deformation; increase fatigue resistance and provide better adhesion between the asphalt and the aggregate (Awwad and Shbeeb, 2007). Grinded polyethylene to provide better coating or attached easily to the aggregate as the surface area of the polymer increases.…”
Section: Plasticmentioning
confidence: 99%
“…2007; Awwad and Hbeeb [31] have investigated the improvement of asphalt modified with polyethylene (PE). Their studies have been also carried out to determine the best type of PE to be used and its proportion in the asphalt mixture.…”
Section: A Case Studiesmentioning
confidence: 99%